Structuring phase and polarization singularity sheets in 2D - Lim, Soon Wei Daniel; ParK, Joon-Suh; Meretska, Maryna L.; Dorrah, Ahmed H.; Capasso, Federico (2021 CONFERENCE ON LASERS AND ELECTRO-OPTICS (CLEO), 2021)
Beyond one-dimensional optical singularity topologies, we demonstrate zerodimensional (point) and two-dimensional (sheet) singularities. We engineer phase and polarization sheet singularities through inverse-design, by maximizing the field phase gradient, and demonstrate metasurface-enabled realizations of each. (C) 2021 The Author(s)